Studi Komparatif Penegakan Hukum Anti Korupsi Militer Terhadap Wewenang KPK dalam Putusan Perkara Nomor 87/PUU-XXI/2023 (International Forum of Researchers and Lecturers, 2025)
The Constitutional Court Decision Number 87/PUU-XXI/2023 affirms the authority of the Corruption Eradication Commission (KPK) to investigate corruption crimes within the military, a step that raises concerns regarding the harmonization of civil and military jurisdictions within Indonesia's legal system. This study employs a normative research method with a comparative law approach and regulatory analysis. A comparative study is conducted with the United States and South Korea to identify the best approaches in handling military corruption. The study highlights the importance of balanced legal reforms that preserve military autonomy while integrating civilian oversight to strengthen anti-corruption efforts. The findings indicate that the involvement of civilian institutions in addressing military corruption can enhance transparency and accountability, despite facing challenges such as institutional resistance. This study recommends synergy between civil and military jurisdictions to establish an effective and equitable law enforcement system.